2003
DOI: 10.1063/1.1579466
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo study of singlet–triplet transition in ethylene

Abstract: A theoretical study is reported of the transition between the ground state ( and the lowest triplet state( ) of ethylene based on the diffusion Monte Carlo (DMC) variant of the quantum Monte Carlo method. Using DMC trial functions constructed from Hartree-Fock, complete active space self-consistent field and multi-configuration self-consistent field wave functions, we have computed the atomization energy and the heat of formation of both states, and adiabatic and vertical energy differences between these state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
(33 reference statements)
9
19
0
Order By: Relevance
“…Although there does not appear to be sufficient experimental data to make a good comparison, we do have the recent high quality CCSD͑T͒/CBS result 45 of 68.8 kcal/mol to compare against, and with which our recommended result of 69.20Ϯ 0.17 kcal/ mol only differs by 0.4 kcal/mol. El Akramine and co-workers 43 also recently studied this transition using QMC to obtain 69.6Ϯ 0.3 kcal/ mol, and our results are in agreement with theirs, even given the differences in our wave functions.…”
Section: B Ethylenesupporting
confidence: 78%
See 1 more Smart Citation
“…Although there does not appear to be sufficient experimental data to make a good comparison, we do have the recent high quality CCSD͑T͒/CBS result 45 of 68.8 kcal/mol to compare against, and with which our recommended result of 69.20Ϯ 0.17 kcal/ mol only differs by 0.4 kcal/mol. El Akramine and co-workers 43 also recently studied this transition using QMC to obtain 69.6Ϯ 0.3 kcal/ mol, and our results are in agreement with theirs, even given the differences in our wave functions.…”
Section: B Ethylenesupporting
confidence: 78%
“…41͒ to 4.6 eV. 42 Calculations have been in better agreement, with results ranging from recent QMC calculations 43,44 both producing 4.50Ϯ 0.02 and 4.51 eV for a CCSD͑T͒/CBS ͑Ref. 45͒ calculation, up to about 4.6 eV for MRCI ͑Ref.…”
Section: B Ethylenesupporting
confidence: 60%
“…In addition to the heat of formation, Nguyen et al 61 reported both vertical (104.1 kcal/mol) and adiabatic (65.6 kcal/mol) excitation energies for the triplet state. Corresponding diffusion Monte Carlo values of 103.5 ± 0.3 kcal/mol (vertical) and 66.4 ± 0.3 kcal/mol (adiabatic) were obtained by El Akramine et al 54 Our best composite adiabatic excitation energy ( 1 A g → 3 A 1 ) is 65.8 ± 0.6 kcal/mol, where the estimated uncertainty assumes the worst case scenario of no cancellation of error in the energy estimates for each state.…”
Section: Twisted 3 a 1 Statementioning
confidence: 55%
“…From the energies 44 calculated at the CCSD(T)/6-311+G(3df,2p)//QCISD/6-311G(d,p) level, a value of ∆E S-T (C 2 H 4 ) ) 64.5 kcal/mol can be derived, including a ZPE correction of 3.2 kcal/mol. Lester and coworkers 45 carried out diffusion Monte Carlo (DMC) calculations on the ground state singlet and first excited triplet state of ethylene at the MP2/6-311++G** geometries, with trial functions constructed from Hartree-Fock, complete active space self-consistent field, and multiconfigurational self-consistent field wavefunctions. Total atomization energies (TAEs) were calculated for the singlet and triplet states at these optimized geometries.…”
Section: Introductionmentioning
confidence: 99%